Negative mood states and related factors in a sample of adolescent secondary-school students in Barcelona (Spain) Estados de ánimo negativos y los factores relacionados en una muestra de adolescentes de enseñanza secundaria de Barcelona - Emily Q. Ahonen; Manel Nebot; Emmanuel Giménez (Elsevier, 2007)
Introduction: Poor mental health is a common problem in adolescence. Little information is available, however, about the factors influencing negative mood states in otherwise healthy adolescents. We aimed to describe the mood states and related factors in a sample of adolescents in the city of Barcelona (Spain). Methods: We administered a health survey to a sample of 2,727 students from public, subsidized, and private schools in Barcelona, aged approximately 14, 16, and 18 years old. To analyze the associations among moods and related factors, we used bivariate logistic regression, and fitted multivariate logistic regressions using the statistically significant variables from the bivariate analysis. To examine the possible group effects of the school on individual students, we employed multilevel analysis. Results: The frequencies of negative mood states increased with age, with girls consistently reporting more frequent negative mood states than boys. The factors associated with negative mood states were problematic alcohol use, perceived mistreatment or abuse, antisocial behavior, intention to use or current use of illegal drugs (not including cannabis), lower perceived academic performance, and feeling isolated. Conclusions: Mood states are influenced by lifestyle and social factors, about which there is little local information. To plan and implement appropriate public health interventions, more complete information about the possible areas of influence is required. To complement the information obtained from studies such as the present study, longitudinal and qualitative studies would be desirable. Introducción: El deterioro de la salud mental es un problema frecuente en la adolescencia. Sin embargo, se sabe poco de los factores influyentes en los estados de ánimo negativos en adolescentes saludables. Pretendemos describir los estados de ánimo negativos y los factores relacionados en una muestra de adolescentes de la ciudad de Barcelona. Métodos: Administramos una encuesta de salud a 2.727 estudiantes de escuelas públicas, concertadas y privadas en Barcelona con edades de 14, 16 y 18 años. Usamos análisis regresión logística bivariada para estudiar las relaciones entre los estados de ánimo negativo y los factores relacionados, para ajustar después un modelo logístico multivariante con los factores significativos del análisis bivariado. Para examinar la posible influencia de los factores grupales de los centros escolares en los individuos, hemos empleado el análisis multinivel. Resultados: Las frecuencias de los estados de ánimo negativos aumentaban con la edad, y las chicas consistentemente relataban estados de ánimo peores que los chicos. El uso problemático del alcohol, el abuso y el maltrato percibido, las conductas antisociales, la intención de usar o el uso actual de drogas ilegales, el bajo rendimiento escolar percibido y el sentirse marginado se relacionaron también con estados de ánimo negativos. Conclusiones: Hay factores personales, sociales y de estilos de vida, sobre los que tenemos poca información local, que influyen sobre los estados de ánimo. Para planear e implementar intervenciones de salud pública apropiadas, necesitamos una información más completa sobre las áreas de posible influencia. Para complementar la información obtenida en estudios como éste, sería deseable llevar a cabo estudios longitudinales y cualitativos.